2008
DOI: 10.1007/s00228-008-0467-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of ACE inhibitors and risk of community-acquired pneumonia: a review

Abstract: The available data suggest that ACE inhibitors may contribute to the reduction of the risk of CAP. Nevertheless, clinical data are scarce and mainly comprise studies including patients of Asian origin. As there seem to be differences regarding the genetic polymorphism of ACE among patients of different origins, future studies are needed that incorporate relevant genetics data that may help clarify the role, if any, of ACE inhibitors in preventing CAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…This already rules out some important potential sources of heterogeneity. For example, through this we exclude ethnicity [4,25] or genetics [2,26] as a potential explanation for variation in results as has been suggested for the association between ACEi use and pneumonia [27]. In other words, this approach increases the likelihood of detecting methodology and data origin as source of biases leading to the heterogeneity in the case-control study findings [28].…”
Section: Discussionmentioning
confidence: 95%
“…This already rules out some important potential sources of heterogeneity. For example, through this we exclude ethnicity [4,25] or genetics [2,26] as a potential explanation for variation in results as has been suggested for the association between ACEi use and pneumonia [27]. In other words, this approach increases the likelihood of detecting methodology and data origin as source of biases leading to the heterogeneity in the case-control study findings [28].…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have shown ACE inhibitors to be somewhat protective against CAP [11,26,[35][36][37] and recurrent pneumonia [11] whereas other studies have failed to find any association [10,38,39]. A critical review performed by Rafailidis et al [40] suggested that ACE inhibitors may contribute to decreased CAP, though most of the studies included in the review showing protective effects comprised of only Asian populations. Other antihypertensive agents have been less studied in CAP; however both beta-blockers and calcium channel blockers have been postulated to increase the risk of pneumonia [41] although the mechanism of risk is unclear.…”
Section: Drug-related Risk Factorsmentioning
confidence: 95%
“…3,4 Recent studies have investigated whether statins and ACEIs have an impact on pneumonia mortality. 2,[5][6][7][8][9][10][11][12] These studies used hospitalised pneumonia patients as their study population and have provided conflicting evidence. In addition, previous studies have also suggested that proton pump inhibitors (PPIs) and Histamine-2-receptor antagonists (H 2 RAs) are associated with pneumonia morbidity because of their gastric acid suppressant action facilitating bacterial colonisation, [13][14][15][16][17] but have not looked at the impact of these drugs on pneumonia mortality.…”
Section: Introductionmentioning
confidence: 99%